Altitude measurement and calibration on miling operation - Nor Hanis, Ahmad Nazri (2013)
ADXL335 accelerometer is an electronic sensor which is used in detecting the acceleration of a moving object in x, y and z axis. In this project the function of the accelerometer had been applied on a platform which can be move in z-axis. This project is all about developing a device where distance can be obtained by manipulating the acceleration from accelerometer. Performing this task will contribute to certain problems that need to be focus in order to get an accurate distance value, such as unknown initial positions of the device on the platform and also the vibration on the accelerometer. There are objectives that had been achieved in this project which includes the implementation of the accelerometer application on shaker, development of a device for accurate distance calculation using accelerometer, and comparison between calculated distance values with the actual value of distance on shaker. First stage of this project is where the accelerometer had been programmed by using a microcontroller board, Arduino Uno. In this Arduino program, the analog reading from accelerometer that had been recorded will be directly converted into acceleration in unit of m/. Simple circuit had been etched before being attached in the device box. During the collection of data, actual distance is being recorded too, to be compared with the calculated distance through double integration method. The device is placed on top of the platform and the original position is being set up before the platform is moved upward and the time is started to be recorded. By using this kind of method, the acceleration and time will be recorded and as the output from this procedure, double integration is being performed and the distance value calculated is being recorded. The result from the calculated distance error will be compared to the actual data where here the percentage error and standard deviation is being analysed. This project had been done very well where all the objectives are a success with the results of average error of 0.27%.